Expression of Oct‐4, SOX‐2, and MYC in dental papilla cells and dental follicle cells during in‐vivo tooth development and in‐vitro co‐culture. (August 2014) - Peng, Zhengjun; Liu, Lu; Wei, Xi; Ling, Junqi
<x xml:space="preserve">Abstract</x> During tooth development, the special structure of dental follicle and dental papilla enables dental papilla cells (DPCs) and dental follicle cells (DFCs) to make contact with each other. Octamer‐binding transcription factor 4 (Oct‐4), sex determining region Y box‐2 (SOX‐2), and cellular homologue of avian myelocytomatosis virus oncogene (MYC) (OSM) are associated with reprogramming and pluripotency. However, whether the expression of OSM could be activated through cell–cell communication is not known. In this study, the distribution of OSM in rat tooth germ was investigated by immunohistochemical staining. An in‐vitro co‐culture system of DPCs and DFCs was established. Cell proliferation, cell apoptosis, cell cycle stages, and expression of OSM were investigated by Cell Counting Kit 8 (CCK8) analysis, flow cytometry, real‐time PCR, and immunohistochemical staining. We found that Oct‐4 and SOX‐2 were strongly expressed in tooth germ on days 7 and 9 after birth, whereas MYC was expressed only on day 9. Cell proliferation and apoptosis were inhibited, the cell cycle was arrested in the G0/G1 phase, and the propidium iodide (PI) value was downregulated. Expression of Oct‐4 and SOX‐2 was significantly elevated in both cell types after 3 d of co‐culture, whereas expression of MYC was not significantly elevated until day 5. These results indicate that the optimized microenvironment with cell–cell communication enhanced the expression of reprogramming markers associated with reprogramming capacity in DPCs and DFCs, both in vivo and in vitro.